Victims and Villains: Gender Representations,Surveillance and Punishment in the Judicial Discourse on Rape - de Carvalho Figueiredo, Debora (International Journal of Speech, Language and the Law, 2001)
The thesis, based on the theories of critical discourse analysis, gender studies and feminist legal studies, carries out an investigation of the judicial discourse used in fifty British appeal court decisions on rape cases. This work aims to investigate the discourse of these legal decisions to see how rape is defined, how rape offenders and rape complainants are described and categorized, and what impact the representations of the event ‘rape’ and its main participants have on the appeal decisions. In addition, the thesis also aims to investigate the role played by the discourse of appeal decisions on cases of rape on processes of education, surveillance, control and discipline of male and female social and sexual behaviour. As far as methodology is concerned, this study looks at the lexico-grammatical choices made by the judicial writers to compose their legal decisions. The different lexical depictions of stranger rapists and known rapists will be used here as a sample of my analyses (all the examples were taken from appeals published in the Criminal Appeal Reports (Sweet & Maxwell) between 1987 and 1998). The appeal decisions analysed in this work indicate that, when judging cases seen as ‘serious’ (i.e. usually committed by men who did not know their victims previously), the appellant is cast in the role of ‘real rapist’ either because: (a) he is depicted as a ‘bad’ character (lack of morals, previous convictions, etc.), or (b) he is depicted as almost deranged (a drug addict, a victim of child abuse, a psychologically unstable person). In the corpus these appellants were characterized as ‘hard criminals’ or as ‘psychologically disturbed’ through lexico-grammatical selections such as: the appellant’s record of violent sexual crime was appalling the appellant was a clear danger to the public he constituted a danger to female members of the public he was completely out of control the offender is, and has clearly demonstrated himself to be, a danger to women the offender was under the influence of drugs at the time of the commission of the offences the further evidence of mental instability contained in the psychiatric reports he came from a family who were generally of dull or very dull intellect. He was sexually abused as a child. He was an unwanted child. he had been drinking and smoking cannabis However, men who raped their present or former partners are not described in the same way. In cases of marital rape, the judicial reasoning is that men who force their present or ex-partners to have sex are led neither by an uncontrollable sexuality nor by criminal tendencies, but rather by a mixture of misplaced love, pain, stress and confusion, usually triggered by the breakdown of their relationships. As such, they do not fit into the category of ‘real’ rapists. The sympathetic portrayal of sexually abusive partners in appeal decisions on rape cases is achieved through a selection of naming patterns and descriptions that depict the assailant within a frame of pain and suffering, and which renders the event as something negative but less serious than other cases of rape. Below are some examples: he is a young man; he is sexually immature he had intended to kill himself a man of positive good character the appellant was emotionally ill he had been a good husband he had been upset by the thought that there was another man in his wife’s affection a man of exemplary character he was diagnosed as suffering from a reactive depression with associated anxiety symptoms, secondary to his wife leaving him he was on an emotional roller coaster the man had been gravely distressed both by the separation and the fact that his wife had a new man in her life In short, the analyses indicate that, from the perspective of judicial discourse, serious rape is stranger rape, women of ‘good’ sexual character are ‘true’ victims, and rape is the result of criminal tendencies or mental problems (in the case of stranger rapists), or of desperation caused by the breakdown of the relationship (in the case of marital rapists). This rather flat picture depicts rape as an isolated crime motivated by an uncontrolled sexual drive or emotional despair, disconnected from social issues such as gender violence, domestic violence, gender asymmetry and the high level of social tolerance to the problem of violence against women, and ultimately influences the length of sentences given to sexually abusive men. The categorization systems used by judicial discourse to evaluate rape express value judgements about how men and women behave, and are part of a pedagogical network involving different discourses (e.g. discourses of the family, religion, moral, education, science) which establishes, supervises, punishes and controls forms of behaviour and of identities.